2013
DOI: 10.1016/j.toxicon.2013.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Attack of the nervous system by Clostridium perfringens Epsilon toxin: From disease to mode of action on neural cells

Abstract: Epsilon toxin (ET), produced by Clostridium perfringens types B and D, ranks among the four most potent poisonous substances known so far. ET-intoxication is responsible for enterotoxaemia in animals, mainly sheep and goats. This disease comprises several manifestations indicating the attack of the nervous system. This review aims to summarize the effects of ET on central nervous system. ET binds to endothelial cells of brain capillary vessels before passing through the blood-brain barrier. Therefore, it induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 109 publications
1
33
0
Order By: Relevance
“…Murrell et al [83] first suggested that exotoxins could be a potential cause of MS, as humans are not natural hosts of C. perfringens types B or D [8487]. Exotoxins bind to receptors present in the vascular system of the brain and in both myelinated and unmyelinated brain regions, such as the corpus callosum [8891]. Osmolysis occurs upon binding to the receptor [9296].…”
Section: Main Textmentioning
confidence: 99%
“…Murrell et al [83] first suggested that exotoxins could be a potential cause of MS, as humans are not natural hosts of C. perfringens types B or D [8487]. Exotoxins bind to receptors present in the vascular system of the brain and in both myelinated and unmyelinated brain regions, such as the corpus callosum [8891]. Osmolysis occurs upon binding to the receptor [9296].…”
Section: Main Textmentioning
confidence: 99%
“…Toxin-dependent cell signaling leading to cell necrosis is not yet fully understood and includes ATP depletion, AMP-activated protein kinase stimulation, mitochondrial membrane permeabilization, and mitochondrial-nuclear translocation of apoptosis-inducing factor, which is a potent caspase-independent cell death factor. The early and rapid loss of intracellular K + induced by ETX and ATX, seems to be the early event leading to cell necrosis [105] (review in [106][107][108]. Change in cell membrane permeability with K + , Ca ++ , and ATP as the main signaling molecules is a common feature of PFTs [109].…”
Section: -Mode Of Actionmentioning
confidence: 99%
“…C. perfringens Etx rapidly disrupts the blood-brain barrier, binds neuronal cells and causes lethality [31,52,56,60]. Among neuronal cell populations, the neurons are most susceptible followed by oligodendrocytes and astrocytes [61].…”
Section: A Veterinary Perspective On Etx: Field and Laboratory Finmentioning
confidence: 99%